2015
DOI: 10.1021/acs.chemmater.5b02145
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial Effects in ε-LixVOPO4 and Evolution of the Electronic Structure

Abstract: The epsilon polymorph of vanadyl phosphate ε-VOPO 4 is a promising cathode material for high-capacity Li ion batteries, owing to its demonstrated ability to reversibly incorporate two lithium ions per redox center. As lithium is inserted into the nanosized particles within the cathode, the electrochemical reaction can be largely affected by the interfacial chemistry at the nanoparticle surface. We performed X-ray photoelectron spectroscopy using both soft (XPS) and hard (HAXPES) X-rays to chemically distinguis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 63 publications
4
32
0
Order By: Relevance
“…For V 2p spectrum of bilayer-VOP nanosheets sample (Figure 5d), the characteristic peak located at 518.3 eV in 2p 3/2 region is assigned to V 5+ , while the nearby split peak at 517.1 eV is the evidence of formation of V 4+ . [11,41] The same resulted can be also observed from the V 2p 1/2 region. While for bulk-VOPO 4 sample, only the characteristic peaks attributed to V 5+ can be detected.…”
Section: Diffusion Kinetics Analysissupporting
confidence: 77%
See 1 more Smart Citation
“…For V 2p spectrum of bilayer-VOP nanosheets sample (Figure 5d), the characteristic peak located at 518.3 eV in 2p 3/2 region is assigned to V 5+ , while the nearby split peak at 517.1 eV is the evidence of formation of V 4+ . [11,41] The same resulted can be also observed from the V 2p 1/2 region. While for bulk-VOPO 4 sample, only the characteristic peaks attributed to V 5+ can be detected.…”
Section: Diffusion Kinetics Analysissupporting
confidence: 77%
“…Considering the various valence change of V in VOPO 4 framework during the electrochemical reaction, the theoretical specific capacity of layered VOPO 4 ⋅2H 2 O should be higher than 300 mAh g −1 . [11,12] Nevertheless, up to date, the reported optimal capacity of VOPO 4 ⋅2H 2 O cathode in aqueous ZIBs is less than 170 mAh g −1 . The main reason should be attributed to the sluggish diffusion of Zn 2+ and strong electrostatic interactions between Zn 2+ and VOPO 4 ⋅2H 2 O host.…”
Section: Introductionmentioning
confidence: 99%
“…showed that the VOPO 4 ↔ LiVOPO 4 reaction is plagued with side reactions, possibly due to the formation of a semireversible SEI. [ 12,40 ] This is shown in Figure 12 , where the measured capacity (red squares) is much larger than the capacity due to V redox (red diamonds). They also mentioned that these side reactions are not observed in nanosized samples which did not undergo HEBM.…”
Section: Synthesis and Its Impact On The Electrochemical Performance mentioning
confidence: 92%
“…It was shown that due to slow Li intercalation kinetics, the second Li starts to intercalate before the intercalation of the first Li is complete, creating a Li concentration gradient within ε‐VOPO 4 nanoparticles. [ 12 ] We will show later, that even in the optimized nanocrystalline ε‐VOPO 4 /graphene material, the rate performance is limited by the slower high‐voltage process, which remains one of the major limitations of this material. [ 13 ]…”
Section: Lixvopo4 (X = 0 1) Polymorphism and Stabilitymentioning
confidence: 99%
“…These phases demonstrate the ability to insert/de‐insert significant amount of Li/Na ions. The oxy polyanionic framework type compounds such as Li x VOPO 4 and Li x TiOXO 4 , (X= S, P and Si) have been also reported for Li insertion and de‐insertion studies . Monoclinic ϵ‐VOPO 4 phase shows insertion of two Li ions with redox couple of V 5+ /V 4+ and V 4+ /V 3+ vs. Li + /Li in the voltage window of 4.5‐2.0 V .…”
Section: Introductionmentioning
confidence: 99%